Shear degradation model of HPAM solutions for the design of regulator valves in polymer flooding EOR - F. A. Díaz; J. P. Torné; A. Prada; G. Perez (Journal of Petroleum Exploration and Production Technology, 2020)
Abstract Polymer flooding for enhanced oil recovery is increasingly in demand in countries such as Colombia, where ECOPETROL has taken major steps in applying this technique to revitalize mature oil fields. The purpose of injecting polymer into reservoirs is to increase the viscosity of the aqueous phase to enhance the mobility ratio. Several aspects can affect and weaken the performance of a polymer flooding operation, however, most of them can be controlled. One of the most important factors is the degradation of the polymer by shear, which causes a reduction in the aqueous phase viscosity. This study was based on work related to the degradation of HPAM solutions induced by the use of regulator valves to control flow and pressure in multiple zones in the same well or multiple wells connected to the same pump. Several tests were completed in a facility designed and prepared to perform regulator valves testing. The results obtained during the initial phase of the testing were compared to computational fluid dynamics simulations, obtaining a shear degradation model which can be used to optimize the design of regulator valves or any other flow control device.